Avaliação clínica da presença da alça de henle em chelonoidis carbonarius (spix, 1824) pelo uso do diurético furosemida - Silva, Ana Clarisse Dias da (2020)
According to the literature, the reptiles would not have a loop of Henle, however, some mention their presence, however with the loss of the ascending portion of it. This region is the site of action of some diuretics, such as furosemide. The objective of this work was to verify if there is an action of this drug in Chelonoidis carbonarius tortoises. Two experiments were carried out: in the first, the time it took the animals to urinate after applying furosemide was evaluated and in the second, the volume of urine produced was quantified. All animals came from the Arruda Câmara Zoobotanical Park, located in the city of João Pessoa-PB, where the experiments were carried out. In experiment 1, animals that received furosemide urinated in a shorter average time (41,83±23,96)when compared to animals that did not receive (90,17±68,99). In experiment 2, there was a significant increase in diuresis after the application of furosemide, with an increase in urine volume equivalent to 177.9%. These results point to the efficacy of furosemide in the species C. carbonarius, therefore, it is concluded that the nephron of the tortoise C. carbonarius presents the ascending portion of the loop of Henle.